GROSS DOMESTIC PRODUCT (GDP) AS A MEANS OF ANALYSIS OF THE SCALE AND RATE OF ECONOMIC GROWTH - Baxronova Nafisa; Umirzoqova Muxabbat Ismatjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Our article is devoted to the analysis of gross domestic product (GDP) as a key indicator for assessing the scale and pace of economic growth. We consider the theoretical foundations of calculating GDP, its role in determining the state of the economy, and the use of this indicator to monitor economic processes at various levels: from individual countries to the global economy. Particular attention is paid to the methods of estimating GDP, as well as the limitations associated with using this indicator as a universal measure of economic growth. The article also presents examples of the use of GDP in the analysis of the dynamics of economic development, and discusses modern challenges such as the instability of global markets and the impact of external factors on growth rates.